About the Contract Theory (about Nobel Prizes on Economy) - Ju. P. Voronov (Мир новой экономики)
The article - is description of Nobel prizes on economy. Nobel Prize in Economics “For the development of the theory of contracts” went to American professors Oliver Hart and Bengt Hallstrom. O. Hart was born in the UK, Swede B. Holmstrom - in Finland. Nevertheless, the history of the two laureates has more to do with the United States than with the historical homeland. Short CV of winners are presented, and summary of contract theory is described. Particular emphasis has been placed on agents opportunistic behavior and on winners works on soviet economic reforms of 1960’s years.